Anti-extractive Rumouring in the Russian North-East - Sardana Nikolaeva (Revue Internationale de Politique de Développement)
This chapter discusses the potentiality of alternative Indigenous politicised discourses, arguing that diverse public narratives can reveal more subtle, yet still effective forms of agency, and, most importantly, highlight the plurality of Indigenous anti-extractive discourses. Building on ethnographic materials, I address the neglected subject of rumours that can open a specific productive space for alternative forms of evidence to understand, write, and most importantly, experience resistance. I demonstrate how localised rumours can mirror uneven power relations between local community, extractive company, and the state. Through the production and reproduction of certain rumouring narratives, the community expresses its fears and anxieties over changing environmental conditions (especially water pollution and radiation), concerns over health, and its members’ precarious and marginalised position within the extensive discourses on economic development, extractive profits and government interventions. Under these conditions of marginality, the community members resist with the only resource they have—rumours—reacting to and, sometimes, subverting their precarious positions.